Microstructural changes during precision machining of thin substrates - Saptaji, K. (2014)
This paper reports investigations in machining of thin substrates with thickness less than 100μm. The machining process induces severe plastic deformation through the thickness of the machined thin workpiece due to the high ratio of the depth of cut to workpiece thickness. The diamond face turning is used to machine thin workpieces down to a thickness less than 100μm. The microstructure of the machined sample is studied and x-ray diffraction used to observe the crystallographic orientation / texture. The microstructures of the thin machined workpieces are seen to become more random, denser, and finer with the shape of the grains less elongated as compare to the bulk and thick machined sample. The x-ray diffraction analyses indicate that machining of thin substrates changes the texture or orientation. Different deformation mechanisms may occur when machining thin workpiece especially at thicknesses below 100μm.